ANALISIS FEEDING PERIODICITY IKAN BETOK (Anabas testudineus Bloch) YANG TERTANGKAP DI PERAIRAN RAWA MALINTANG BARU KECAMATAN GAMBUT KABUPATEN BANJAR PROVINSI KALIMANTAN SELATAN - Elrifadah Elrifadah (Universitas Lambung Mangkurat, 2015)
This study aims to determine the periodicity feeding climbing perch caught in the waters of the swamp Malintang-Baru district-Gambut-Banjar district of South Kalimantan. The number of samples of fish caught 180 tail using fishing gear cash net. pick up a fish sampling during 24 hours, with an interval of 4 hours, ie at 20.00, 24.00, 04.00, 08.00, 12.00, and 16.00. Feeding periodicity analysis performed by calculating the fullness of the stomach contents are expressed as a percent. To determine the relationship between feeding periodicity with the fullness of the stomach contents, use statistical tests completely randomized design (CRD). The analysis showed that feeding periodicity affect the fullness of the stomach contents, at 20:00 fullness of stomach contents which is 80.9191% of maximum fish activity etching in taking food. At 24.00 (50.9722%) and 12.00 (47.7563%) of the climbing perch also actively take food, but not as active at 20:00. whereas 04.00 (12.4054%), 08.00 (21.1733%), and 16.00 (7.1414%) say of the climbing perch not perform activities takers.